Communication in the Hospitality and Service Industry: Systematic Literature Review Based on PRISMA - Dede Sugandi (CV. Ulil Albab Corp, 2026)
Communication is a fundamental element in the hospitality and service industry that directly influences service quality, customer satisfaction, and organizational performance. This study presents a systematic literature review employing the PRISMA 2020 framework (Page et al., 2021) to identify, select, and analyze scientific literature related to communication in the hospitality and service industry. A comprehensive database search was conducted across Google Scholar, Scopus, and DOAJ covering publications from 2021 to 2025. Of the 312 initially identified articles, 38 met the inclusion criteria and were thoroughly analyzed. Key findings reveal: (1) interpersonal communication is a primary determinant of customer satisfaction; (2) employee communication soft skills significantly impact service quality perceptions; (3) AI-driven digital communication is increasingly dominant post-COVID-19; (4) cross-cultural communication barriers remain a major challenge; and (5) organizational internal communication quality influences guest service performance. These findings carry practical implications for designing effective communication training programs and adaptive organizational communication strategies in the digital era.